Edukasi Dan Pendampingan Penyusunan Laporan Keuangan UMKM Kuliner XYZ - agung dinarjito; Aldi Bilqisthy Pratama; Dessyka Sitanggang; Faizul Abrori; Fayiz Alfitra RM; Lamhot Doli Tambunan; Muhammad Arfan; Muhammad Rajul Muzik; Muhammad Taufiq Hidayat; Nanda Sulfiandra; Putra Jaya Bukit (Pengmasku, 2021)
This community service activity aims to provide education and assistance for Micro, Small and Medium Enterprises (MSMEs) by providing an understanding of the importance of preparing financial reports and providing assistance in preparing financial reports using the SI APIK application. The method of implementing the activity is carried out in several stages, namely the first stage is planning and observation, the second stage is assistance in the preparation of financial reports using the Si APIK application, the third stage is the preparation of financial reports until August 2021, and the last stage is making video tutorials using the SI APIK application and making posters regarding the preparation of financial reports. MSME XYZ which is engaged in the culinary field is the object chosen and located in Central Java. The result of this activity is that MSME XYZ is able to make financial reports for the month of August using the Si APIK application. Kegiatan pengabdian masyarakat ini bertujuan untuk mmeberikan edukasi dan pendampingan bagi usaha Mikro, Kecil, dan Menengah (UMKM) dengan memberikan pemahaman tentang pentingnya penyusunan laporan keuangan dan memberikan pendampingan penyusunan laporan keuangan menggunakan aplikasi SI APIK. Metode pelaksanaan kegiatan dilakukan dengan beberapa tahap, yaitu tahap pertama adalah perencanaan dan observasi, tahap kedua adalah kegiatan pendampingan penyusunan laporan keuangan menggunakan aplikasi Si APIK, tahap ketiga penyusunan laporan keuangan sampai dengan bulan Agustus 2021, dan tahap terakhir adalah pembuatan video tutorial penggunaan aplikasi SI APIK dan pembuatan poster mengenai penyusunan laporan keuangan. UMKM XYZ yang bergerak dibidang kuliner merupakan obyek yang dipilih dan berlokasi di Jawa Tengah. Hasil kegiatan ini adalah bahwa UMKM XYZ mampu membuat laporan keuangan bulan Agustus dengan menggunakan aplikasi Si APIK.